Synthesis and Crystal Structure of 3,3'-Dimethyloxy-1,1'-[butane-1,4-diyldioxybis(nitrilomethylidyne)]dibenzene - Wang, Li; Wu, Jun-Jiang; Zhang, Yang; Li, Gang; Li, Xiang (Asian Journal of Chemistry, 2013)
The compound 3,3'-dimethyloxy-1,1'-[butane-1,4-diyldioxybis(nitrilomethylidyne)]dibenzene with the m.f. C20H24N2O4, was synthesized by the reaction of 3-methoxybenzaldehyde with 1,4-bis(aminooxy)butane in ethanol. The molecule, which lies about an inversion centre, adopts a linear structure, in which the oxime groups and benzene ring systems assume an anti conformation. The intramolecular interplanar distance between parallel benzene rings is 0.901(3) Å. Weak intermolecular C10-H10B···O2 hydrogen bonds link two other molecules into infinite zig-zag supramolecular structure.